Penerapan TPACK dalam Pembelajaran Akidah Akhlak Guna Meningkatkan Hasil Belajar Siswa MI - Munawir; Novi Ernawati; Vika Mustaqotul Firdaus (STIKes Ibnu Sina Ajibarang, 2024)
The purpose of writing this article is to apply TPACK in improving student learning outcomes in the Islamic Aqidah Akhlak subject. Learning Aqidah Akhlak is an important component in religious education in MI/SD. However, students tend to be less interested in learning moral principles. The use of technology is one way for educators to improve student learning outcomes. In realizing this, every educator must have and understand Technological Pedagogical Content Knowledge (TPACK). TPACK is a collaboration between 3 basic components namely Technology Knowledge, Pedagogical Knowledge, and Content Knowledge. This study uses a qualitative approach with the method of literature study. In this study, data collection included collecting literature from journals, articles and other sources, as well as related to the topics of discussion that were made. Technology is very useful and very helpful for teacher tasks which lie in planning, implementing, evaluating, and following up. With the existence of technology in the current era, it can be used as a media tool to help the learning process of akidah moral subjects to develop aspects of students' motivation, courage, and creativity.